1999
DOI: 10.1093/emboj/18.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the recognition of superantigen streptococcal pyrogenic exotoxin A (SpeA1) by MHC class II molecules and T-cell receptors

Abstract: Streptococcal pyrogenic exotoxin A (SpeA) is a superantigen produced by Streptococcus pyogenes and is associated with severe infections characterized by rash, hypotension, multiorgan failure and a high mortality rate. In this study, an allelic form of this toxin, SpeA1, was crystallized with four molecules in the crystallographic asymmetric unit and its crystal structure was determined at 2.6 Å resolution. The crystallographic R-factor was 19.4% (33 497 reflections) for 7031 protein atoms and 88 water molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 66 publications
1
66
0
Order By: Relevance
“…Of the mutant SPEA proteins assayed, only the C90A mutant, and combinations thereof, resulted in complete elimination of the dimer species. These results strongly indicate that the observed protein dimer was formed by an intermolecular disulfide bond between the C90 residues of two separate SPEA molecules, as was previously proposed by Papageorgiou et al [6].…”
Section: Dimerizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Of the mutant SPEA proteins assayed, only the C90A mutant, and combinations thereof, resulted in complete elimination of the dimer species. These results strongly indicate that the observed protein dimer was formed by an intermolecular disulfide bond between the C90 residues of two separate SPEA molecules, as was previously proposed by Papageorgiou et al [6].…”
Section: Dimerizationsupporting
confidence: 88%
“…The X-ray crystal structure of SPEA has been solved at 2.6-Å resolution [6], revealing N-and C-terminal subdomains, and a surface loop constrained by a disulfide bond between residues C87 and C98. In addition, another cysteine (located at position 90) is also inside this loop (Fig.…”
Section: Subject Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the group II (SEB and SEC 3 ) and III (SEA) SAgs that have been structurally characterized in complex with MHC␣, each have similar "footprints" on MHC␣, although SEA is rotated slightly away from HLA-DR1, presenting a smaller contact surface (8) with a reduced affinity (31,59). Not surprisingly, the molecular surfaces of the ␤-barrel domains in group II and group III SAgs, which also includes SpeA and SSA (60,61), are generally similar.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, Kline and Collins reported (27) that the new SpeA3 toxin variant was more mitogenic and had tenfold higher affinity for the class II MHC molecule than the old SpeA1 variant. Crystal structure analysis revealed that the two amino acid replacements, Gly80Ser in SpeA2 and Val76Ile in SpeA3, are located close to a zinc-binding site in SpeA1, a region postulated to be involved in class II MHC recognition (28,29). Taken together, the results suggest that clones expressing the mutant toxins might have more severe effects in vivo.…”
Section: Figurementioning
confidence: 85%